Synthesis and free radical scavenging activity of 2-alkyl/arylchalcogenyl-N-(4-aryl-1, 3-thiazol-2-yl)acetamide compounds. Issue 9 (2nd March 2016) - Wolf, Lucas; Quoos, Natália; Mayer, João C.P.; de Souza, Diego; Sauer, André C.; Meichtry, Luana; Bortolotto, Vandreza; Prigol, Marina; Rodrigues, Oscar E.D.; Dornelles, Luciano
Graphical abstract: Abstract: The synthesis of a new series of organochalcogen-derivatives, 2-alkyl/arylchalcogenyl- N -(4-aryl-1, 3-thiazol-2-yl)acetamides5a –r, provided products in satisfactory yields, which varied from 42% to 95%. All these novel compounds were screened for their in vitro free radical scavenging activity against 2, 2-diphenyl-2-picrylhydrazyl (DPPH) and 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals. Compounds5 (m, h, i, f, q, g, l, c, n ) were effective scavengers against the ABTS radical species but less effective on scavenging the DPPH radical, indicating that the antioxidant effect of these compounds were related to protonated radical scavenger activity.